Molecular dynamics simulation of an argon cluster filled inside carbon nanotubes - 崔树稳 朱如曾 王小松 杨洪秀 (Chinese physics B, 2014)
The effects of the diameters of single-walled carbon nanotubes （SWCNTs） （7.83A to 27.40A） and temperature （20 K-45 K） on the equilibrium structure of an argon cluster are systematically studied by molecular dynamics simulation with consideration of the SWCNTs to be fixed. Since the diameters of SWCNTs with different chiralities increase when temperature is fixed at 20 K, the equilibrium structures of the argon cluster transform from monoatomic chains to helical and then to multishell coaxial cylinders. Chirality has almost no noticeable influence on these cylindrosymmetric structures. The effects of temperature and a non-equilibrium sudden heating process on the structures of argon clusters in SWCNTs are also studied by molecular dynamics simulation.